2018
DOI: 10.3389/fphys.2018.00142
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Web-Based Feedback on Physical Activity and Cardiovascular Health of Nurses Working in a Cardiovascular Setting: A Randomized Trial

Abstract: A disconcerting proportion of Canadian nurses are physically inactive and report poor cardiovascular health. Web-based interventions incorporating feedback and group features may represent opportune, convenient, and cost-effective methods for encouraging physical activity (PA) in order to improve the levels of PA and cardiovascular health of nurses. The purpose of this parallel-group randomized trial was to examine the impact of an intervention providing participants with feedback from an activity monitor coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 53 publications
1
46
1
Order By: Relevance
“…A further six studies reported no significant change in health or physical symptoms [75,126,130,131,147,168], as measured by Short Form-36 [130,147,168], SCL-90 [147], health complaints [75], GHQ [126], or cardiovascular health (i.e., resting blood pressure, [131]). Of the six studies reporting no changes in measures of health or physical symptoms, three were RCTs [75,130,131], and three were non-randomised controlled studies [126,147,168]. The interventions failing to demonstrate positive outcomes used PA [130,131], PA with mindfulness [126], PA with stress education [75], mindfulness [147] and art-based relaxation [168].…”
Section: Health Risk Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…A further six studies reported no significant change in health or physical symptoms [75,126,130,131,147,168], as measured by Short Form-36 [130,147,168], SCL-90 [147], health complaints [75], GHQ [126], or cardiovascular health (i.e., resting blood pressure, [131]). Of the six studies reporting no changes in measures of health or physical symptoms, three were RCTs [75,130,131], and three were non-randomised controlled studies [126,147,168]. The interventions failing to demonstrate positive outcomes used PA [130,131], PA with mindfulness [126], PA with stress education [75], mindfulness [147] and art-based relaxation [168].…”
Section: Health Risk Factorsmentioning
confidence: 99%
“…Thirty-five studies included some form of PA [60,69,75,76,78,83,88,96,98,. The PA interventions included walking [83,88,96,113,115,119,123,127,131,133,136], standing [119], aerobics [60,75], aerobics and resistance exercise [118], yoga [116,122,125,126,132,135], Tai-Chi [130], endurance training [117], muscle strength promotion [117,128], stretching [119,134,137], daily exercise [78,121], physiotherapy exercise [76], exercises with equipment (stair-stepper: [114], treadmill, Wii TM : [96,115], elastic bands and kettlebells [120,137,138], back muscle exercises [98,…”
Section: Physical Activity and Dietary Interventionsmentioning
confidence: 99%
See 3 more Smart Citations